Exhibitions in the age of performance: reflecting on the performativity of art exhibitions in Singapore, 1996-present - Muhammad Ridzal Bin Abdul Hamid (Nanyang Technological University, 2023)
A common assumption held about art exhibitions is that they present objective art historical facts, or even truth about society or the human condition made manifest in works of art. The rise of post-truth politics in recent years, however, has brought into question the way we perceive objective facts and come to accept them as truth. The post-truth political (and media) culture privileges the presentation and framing of points of view to appeal to emotions and personal beliefs over the substance of what is presented. Art exhibitions are no less susceptible to being marshalled in the same way, especially in a state like Singapore that regularly deploys performative tropes and strategies to enact much of its desired political, social and cultural reality, with exhibitions organised, especially by state-run institutions, to serve the state’s agenda of nation-building and identity-formation. These exhibitions are performative in the sense posited by J. L. Austin, in that they do not merely present, or display ‘some state of affairs, or to “state some fact”, which [they] must do either truly or falsely’, but are part of, the doing of actions. Therefore, it is timely and pertinent to question the commonly-held assumption that art exhibitions in Singapore function merely as neutral, objective displays of works of art. Rather, it is necessary now, more than ever before, to study art exhibitions in Singapore as performance, to understand what exactly it is that they perform and how they do so. This thesis will consider the ways that the notion of performance relate to practices of exhibition-making and examine how art exhibitions behave as performance. Secondly, this present study will examine how state-run institutions that exhibit art in Singapore, particularly the Singapore Art Museum (SAM) and the National Gallery Singapore (NGS), perform state-prescribed scripts and agenda to assert the centrality of Singapore within Southeast Asia to the rest of the world. Thirdly, as a counterpoint to the ways state-run institutions perform, this thesis will consider how independent and alternative exhibition-makers perform their autonomy from the state and their alterity to state-run exhibition-making institutions, while also examining the limitations faced by these exhibition-makers in asserting their alterity and independence.